1997
DOI: 10.1038/sj.sc.3100357
|View full text |Cite
|
Sign up to set email alerts
|

Multiple thoracic disc herniations: case report and review of the literature

Abstract: The incidence of intervertebral disc herniation in the thoracic region of the spine is much less than in the cervical or lumbar areas, and multiple thoracic disc herniations are rare. We described a 33-year-old man with two-level thoracic disc herniation, who exhibited features of spinal cord compression. Magnetic resonance imaging and computed tomographic myelography demonstrated anterior compression of the spinal cord due to disc herniation at T4/5 and T7/8 levels. Through an anterolateral approach, these di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 18 publications
(28 reference statements)
0
32
0
2
Order By: Relevance
“…Some authors reported that anterior or antero-lateral discectomy may be the simplest and most effective method for disc excision and relief of spinal cord. 4,13,14 Furthermore, Vanichkachorn and Vaccaro 6 reported that posterior laminectomy was controversial for the treatment of symptomatic thoracic disc protrusions and recommended that the operative procedure must be chosen carefully among the anterior, lateral and posterior approaches. The avoidance of the posterior approach might be related to the fact that posterior laminectomy of the thoracic spine characterized by kyphosis would not successfully lead to decompression of the spinal cord compressed by posterior bulged disc and, furthermore, the spinal cord could be easily damaged when performing disc removal via posterior Figure 2 The excised sequestrated disc was a ring-like form.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that anterior or antero-lateral discectomy may be the simplest and most effective method for disc excision and relief of spinal cord. 4,13,14 Furthermore, Vanichkachorn and Vaccaro 6 reported that posterior laminectomy was controversial for the treatment of symptomatic thoracic disc protrusions and recommended that the operative procedure must be chosen carefully among the anterior, lateral and posterior approaches. The avoidance of the posterior approach might be related to the fact that posterior laminectomy of the thoracic spine characterized by kyphosis would not successfully lead to decompression of the spinal cord compressed by posterior bulged disc and, furthermore, the spinal cord could be easily damaged when performing disc removal via posterior Figure 2 The excised sequestrated disc was a ring-like form.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic herniated thoracic discs (HTDs) account for only 0.15-1.8 % of all intervertebral disc abnormalities treated surgically [1][2][3]. Hott et al [4] defined giant herniated thoracic discs as those ''occupying more than 40 % of the spinal canal based on pre-operative computed tomography (CT) myelography, magnetic resonance imaging (MRI) or both''.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the literature, only 15 patients undergoing noncontiguous, multiple-level HTD decompression have previously been reported. 4,7,11,22,28,34,35 In addition, when considering our global cohort of patients with single-level and multiple-level HTDs, a substantial number of HTDs (n = 59) were deemed asymptomatic and nonoperative. Therefore, all surgical HTDs in myelopathic patients abutted, distorted, and deformed the spinal cord, while the surgical HTDs in radiculopathic patients correlated to the level of symptomatology.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…4,8,15 Anterolateral approaches, consisting of thoracotomy or thoracoscopy, best address large, midline, calcified disc herniations. 10,16,28,34,35,39,45 We report our experience on the management of patients with multiple-level symptomatic HTDs, treated via thoracotomy, thoracoscopy, and/or posterolateral approaches. Patient characteristics, surgical variables, and outcomes are compared among the different approaches and also to those of an unmatched cohort of patients undergoing single-level HTD decompression.…”
mentioning
confidence: 99%